The complete stems and branches : time and space in traditional acupuncture - Golding, Roisin; ScienceDirect eBooks (Edinburgh ; New York : Churchill Livingstone/Elsevier, 2008)
This exciting and comprehensive book gives a clear, detailed and accessible presentation of the stems and branches theory of acupuncture. The majority of the principles behind Stems and Branches underlie the whole of acupuncture, regardless of the system being used. Fundamental principles are outlined in a clear manner and each chapter covers philosophical theory in depth and uses practical examples and exercises throughout, allowing any practitioner to integrate this form of acupuncture into practice as they progress throughout the book. Easy to follow and easy to use, the book will guide practitioners in the use of a patient's Stem and Branches birth chart to allow them to combine this information with their own therapeutic approach to formulate tailor-made treatments for each client. First fully comprehensive book to explore all of the concepts involved in Stems and Branches and to deal with its wider application. Clearly illustrated throughout to clarify concepts and present information in an accessible way. Applies theory to clinical practice through the use of practical examples and exercises. Fundamental principles outlined in a clear manner. Easy to follow and easy to use. Includes Glossary, Recommended Reading List, year charts and b1(Benergy calculator'disk.s
Cyclical time -- Sequential time -- Non-time -- The calendar -- Heaven, earth and humankind (Tian, Di, Ren) -- Wu Xing: five elements -- Six divisions --Great movements -- Stem organs -- Branches (Di Zhi) -- Putting it all together -- Open-hourly method of point selection -- The Chinese sky -- Psychological profiles -- Numerology -- Symbols.
Includes bibliographical references (pages 297-299) and index.
Print version record.
Elsevier
Keywords: Acupuncture; Acupuncture; Acupuncture Therapy -- methods; Medicine, Chinese Traditional; Electronic books